Characterization and Modeling of Nano-organic Thin Film Phototransistors Based on 6,13(Triisopropylsilylethynyl)-Pentacene: Photovoltaic Effect - Jouili, A.; Mansouri, S.; Al-Ghamdi, Ahmed A.; El Mir, L.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2017)
Organic thin film transistors based on 6,13(triisopropylsilylethynyl)-pentacene (TIPS-pentacene) with various channel widths and thicknesses of the active layer (300 nm and 135 nm) were photo-characterized. The photoresponse behavior and the gate field dependence of the charge transport were analyzed in detail. The surface properties of TIPS-pentacene deposited on silicon dioxide substrate were investigated using an atomic force microscope. We confirm that the threshold voltage values of the TIPS-pentacene transistor depend on the intensity of white light illumination. With the multiple trapping and release model, we have developed an analytical model that was applied to reproduce the experimental output characteristics of organic thin film transistors based on TIPS-pentacene under dark and under light illumination.
Keywords: Nano-materials; organic-TFTs; photovoltaic effect; modeling